Consequences of gamma radiation to mice skin - Chávez Soto, Blanca (2000)
OBJECTIVE: To determine clinical, biochemical, hematologic and histopathologic effects caused by gamma radiation to mice skin. MATERIAL AND METHODS: Experimental case-control study in 30 albino Balc-10 mice irradiated with fractionated doses, 1.2, 1.8, 3.0, and 3.6 Gy, during 3 sessions with one week interval. RESULTS: Alterations produced with radiation threshold values below 3 Gy were directly related to dose increase, with inverse effect noted above threshold values and remarkable organism response to detrimental action. There was marked reduction in blood cells, mainly lymphocytes. CONCLUSIONS: Gamma irradiation produces various effects that depend on dosage and number of irradiations.